Complementary description of Labidocera bataviae Scott, 1909, L. madurae Scott, 1909 and L. pavo Giesbrecht, 1889 (Copepoda, Calanoida, Pontellidae) in Indonesian waters - Mulyadi; Sidabalok, Conni M.; Haryono (Zootaxa, 2023)
Three species of Labidocera from Indonesian waters are herein redescribed based on topotypic material. Labidocera bataviae Scott, 1909, L. madurae Scott, 1909, and L. pavo Giesbrecht, 1889 are superficially similar in morphology that may easily be mistaken for each other. L. madurae is characterized by a moderately large and asymmetrical Ur1, with the middle of the right and the left sides considerably inflated; the CR almost symmetrical, the Ri’s of P5 asymmetrical, right side is longer, conically shaped and with tapered end, while the left side is short with rounded apex; Re armed with 3 unequal St in female. The male is characterized by the chela of the right P5 with stout and distally curved thumb, outer margin between thumb and distal end of Re1 naked, and the Re2 of the left P5 elongated, oval-shaped, and twice as long as wide: with 1 outer spine and 3 unequal terminal processes. Labidocera bataviae female is distinguishable by a moderately large and asymmetrical Ur1, with the right and left margins each armed with one knob-like process, and by the form of P5; the male by the bifurcated thumb of chela of the right P5. L. pavo female is distinguishable by having two large conical lobes on Ur1, and the form of P5; the male by the short thumb of chela of the right P5.